Oral communication in individuals with hearing impairment—considerations regarding attentional, cognitive and social resources - Lemke, Ulrike; Scherpiet, Sigrid (Frontiers in Psychology, 2015)
Traditionally, audiology research has focused primarily on hearing and related disorders. In recent years, however, growing interest and insight has developed into the interaction of hearing and cognition. This applies to a person’s listening and speech comprehension ability and the neural realization thereof. The present perspective extends this view to oral communication, when two or more people interact in social context. Specifically, the impact of hearing impairment and cognitive changes with age is discussed. In focus are executive functions, a group of top-down processes that guide attention, thought and action according to goals and intentions. The strategic allocation of the limited cognitive processing capacity among concurrent tasks is often effortful, especially under adverse communication conditions and in old age. Working memory, a sub-function extensively discussed in cognitive hearing science, is here put into the context of other executive and cognitive functions required for oral communication and speech comprehension. Finally, taking an ecological view on hearing impairment, activity limitations and participation restrictions are discussed regarding their psycho-social impact and third-party disability.